2021
DOI: 10.1038/s41467-021-25146-w
|View full text |Cite
|
Sign up to set email alerts
|

The sugar-responsive enteroendocrine neuropeptide F regulates lipid metabolism through glucagon-like and insulin-like hormones in Drosophila melanogaster

Abstract: The enteroendocrine cell (EEC)-derived incretins play a pivotal role in regulating the secretion of glucagon and insulins in mammals. Although glucagon-like and insulin-like hormones have been found across animal phyla, incretin-like EEC-derived hormones have not yet been characterised in invertebrates. Here, we show that the midgut-derived hormone, neuropeptide F (NPF), acts as the sugar-responsive, incretin-like hormone in the fruit fly, Drosophila melanogaster. Secreted NPF is received by NPF receptor in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 109 publications
(195 reference statements)
12
105
1
Order By: Relevance
“…Given that gut-derived NPF binds to its receptor on the APCs to inhibit Akh release ( Yoshinari et al, 2021 ),that skeletal muscle-derived unpaired 2 (upd2; FBgn0030904) regulates hemolymph Akh levels ( Zhao and Karpac, 2017 ), and that circulating peptides such as Allatostatin A (AstA; FBgn0015591), Drosophila insulin-like peptides (Dilps), and activin ligands influence Akh pathway activity ( Ahmad et al, 2020 ; Hentze et al, 2015 ; Post et al, 2019 ; Song et al, 2017 ), it is clear that a systematic survey of circulating factors that modulate Akh production, release, and Akh pathway activity in each sex will be needed to fully understand the sex-specific regulation of fat storage. Another important point to address in future studies will be confirming results from previous studies that the fat body is the main anatomical focus of Akh-dependent regulation of fat storage ( Bharucha et al, 2008 ; Grönke et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that gut-derived NPF binds to its receptor on the APCs to inhibit Akh release ( Yoshinari et al, 2021 ),that skeletal muscle-derived unpaired 2 (upd2; FBgn0030904) regulates hemolymph Akh levels ( Zhao and Karpac, 2017 ), and that circulating peptides such as Allatostatin A (AstA; FBgn0015591), Drosophila insulin-like peptides (Dilps), and activin ligands influence Akh pathway activity ( Ahmad et al, 2020 ; Hentze et al, 2015 ; Post et al, 2019 ; Song et al, 2017 ), it is clear that a systematic survey of circulating factors that modulate Akh production, release, and Akh pathway activity in each sex will be needed to fully understand the sex-specific regulation of fat storage. Another important point to address in future studies will be confirming results from previous studies that the fat body is the main anatomical focus of Akh-dependent regulation of fat storage ( Bharucha et al, 2008 ; Grönke et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that the release of NPF in EECs is induced not only by mating but is also sugar-dependent, and has a function similar to that of incretins in mammals ( Yoshinari et al, 2021 ). When D. melanogaster is reared on food that excludes sugar, intestinal NPF secretion is suppressed, and NPF release is induced by sugar refeeding.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…When D. melanogaster is reared on food that excludes sugar, intestinal NPF secretion is suppressed, and NPF release is induced by sugar refeeding. When intestinal NPF function is suppressed, D. melanogaster exhibits various metabolic dysfunction such as, lipodystrophy, hyperphagia, and hypoglycemia ( Yoshinari et al, 2021 ), which is partly reminiscent of the function of mammalian PYY ( Schalla et al, 2021 ). This sugar-dependent NPF release is partly mediated by the sugar transporter Sut1, which is expressed in NPF-positive EECs.…”
Section: Remaining Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that AKHs affects expression of orexigenic factors such as CCHamide-2 and neuropeptide F as well as metabolic-related genes like corazonin, limostatin, and ILPs [ 99 ]. In the case of NPF the opposite interaction was confirmed, when this peptide regulates lipid metabolism through AKHs signaling [ 100 ]. Interactions in metabolism regulation between glucagon and neuropeptide Y (NPY) were also shown in mammals in experiments conducted on pigs [ 101 ] and on isolated mice pancreatic islets [ 102 ].…”
Section: Peptides–neuropeptides–hormonesmentioning
confidence: 99%